Optimization of 3,4-Dimethoxychalcone and Rutin Containing Gel with Simplex Lattice Design and In Vitro-In Vivo Test as a Sunscreen - Fatimi, Hana Anisa; Zulkarnain, Abdul Karim; Laksitorini, Marlyn Dian (Pharmaceutical Sciences and Research, 2023)
3,4-Dimethoxychalcone and rutin, a flavonoid that contains chromophore groups, can absorb UV light and thus can be developed as a sunscreen. The objective of this study was to determine the optimum formula of 3,4-dimethoxychalcone and rutin containing gel, evaluate its physical stability, and activity of 3,4-dimethoxychalcone and rutin gel as a sunscreen through in vitro and in vivo tests. HPMC, CMC-Na, and methylcellulose were formulated into a gel base to obtain good adhesion and a clear appearance gel. Simplex Lattice Design (SLD) with Design Expert software version 10 was utilized to determine the optimum gel formulation. UVA-PF protection, photostability with transpore method, and acute dermal irritation test were performed to evaluate sunscreen activity of 3,4-dimethoxychalcone and rutin gel. The data were analyzed using SPSS version 25. The results showed that the optimum formula for 3,4-dimethoxychalcone-rutin gel consisted of 1.5% HPMC, 1.8% CMC-Na and 0.6% methylcellulose, which showed a pH of 6.96, viscosity of 89.10 dpa.s, and spreadability of 16.30 cm2. The pH, viscosity, and spreadability of base and 3,4-dimethoxychalcone- rutin gel was stable for 4 weeks of storage. The UVA-PF value is 6.48 which according to the FDA is included in the category of a two star (**) sunscreen label. The sunscreen did not exhibit a shift in wavelength after 6 hours of irradiation. Based on the primary irritation test, 3,4-dimethoxychalcone- rutin sunscreen produced zero (0) erythema and edema index. Thus, it did not cause irritation to the skin of experimental animals. Therefore, the gel containing 3,4-dimethoxychalcone and rutin had potential as a sunscreen product based on in vitro-in vivo tests and was safe on animal skin.